Longıtudinal Evaluation Of The Predıctıon Of Mandıbular Growth Rotatıon - Dilek Erdem; Ufuk Toygar Memikoğlu; Erhan Özdiler; Serhat Özsoy; Ensar Başpınar (Galenos Yayinevi, 1996)
The purpose of this study was to estimate the possibility of predicting the direction and the amount of growth rotation of the mandible on the basis of morphologic criteria observed on a single lateral cephalometric film at prepubertal stage. The sample consisted of twenty-seven individuals in whom the actual mandibular growth rotation was determined from arbitrary implant line at the time of puberty. A total of 24 morphologic variables were utilized from first lateral cephalometric films. Correlation and stepwise regression analysis were performed between observed mandibular growth rotation during the pubertal period and morphologic variables from first profile radiograph. According to the results, anterior lower facial height and facial axis angle explains 46.1% of true mandibular rotation. Also when there is an anterior rotation inclination in the mandible, lower facial height decreases and facial axis angle increases.